EXPLORING ISLAMIC BANKING SWITCHING INTENTION - Barid, Miftah; Siswanto, Siswanto; Masyhuri, Masyhuri (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Islamic banking is developing quite rapidly, but its market share is still far behind conventional banks. The movement of customers from conventional banks to Islamic banks must be continuously improved. The transfer of conventional bank customers to Islamic banks is determined by the intention to move (Switching intention). Switching intention is an individual's desire or intention to switch services and is described as a signal and opportunity for customers to switch to new services. This study aims to analyze the factors that affect the switching intention of customers of Islamic banks in Malang City with a theory of planned behavior. This study uses a quantitative approach. The number of samples is 100 respondents. Data analysis using confirmatory factor analysis (CFA). The analysis results show that attitude, subjective norm, and perceived behavior control influence the switching intention of Islamic banks in Malang City. The attitude variable is the dominant factor affecting switching intention.